The role of guidance and counseling teachers in reducing bullying behavior through psychoeducation groups - Wahyu Almizri; Firman Firman; Netrawati Netrawati (Universitas Negeri Padang, 2022)
Violence that occurs in adolescents is a form of behavior that is often encountered and the trend continues to increase. One of the violence that occurs in the school environment is bullying. Bullying is violent behavior that is perpetrated by someone against a group of weak people repeatedly by taking advantage of an imbalance of power, which is done physically, verbally or psychologically. Guidance and counseling teachers have a role in providing assistance to students so they can know and accept themselves and can know and accept their environment positively and dynamically. And being able to make decisions. Directing and realizing oneself effectively and productively for the future. In cases of violence that occur, especially bullying, of course this is an urgency for the counseling teacher to be able to reduce this behavior, one of which is with the psychoeducation group. This paper will provide stages in the implementation of psychoeducation because this paper is a literature review that comes from several references.